Research on foreign direct investment and renewable electricity industry nexus in Africa / Ahmed Rashed Ahmed - Ahmed Rashed , Ahmed (2023)
In addition to three introductory chapters, this doctoral thesis incorporates a collection of five empirical research papers on Foreign Direct Investment (FDI) and Renewable Electricity Industry (REI) in Africa. It suggests actionable recommendations on Africa's electricity insecurity issues. Those issues worsen daily, aggravating all facets of African life. In 2019, the International Energy Agency (IEA) estimated that 600 million Africans lived without electricity access and about 900 million lacked healthy cooking facilities in Sub-Saharan Africa (SSA), which particularly suffers from a clear shortage of published renewable energy data and studies. Africa's rapid population growth is another concern, coupled with a growing renewable energy financing gap. As a response to Africa's limitless renewable resources, the IEA recommends stimulating green FDI and renewable electricity production (REP). The first paper is entitled "Determinants of FDI in REI in Africa". A novel dataset of FDI corporations in the REI during 2003–2019 has been obtained. Using the FDI panel gravity fixed effects Poisson pseudo-maximum likelihood model, the uselessness of changes in fossil fuel subsidies in stimulating green FDI is revealed. However, a 1% growth in Africa's gross domestic product (GDP) expands FDI by almost 1.5%. Furthermore, increasing the number of educated African children and raising awareness of renewable energy contribute constructively to REI development. Besides, to understand the green FDI-REP relationship, the second paper, entitled "the nexus among FDI in the REI, REP, and GDP in Africa," is conducted to inspect the existence and nature of co-integration and causality nexuses among these variables in 32 African countries over 2003–2019. Applying the panel vector autoregression model based-Granger causality test and a static panel data approach, a unidirectional Granger causality/growth hypothesis between REP and GDP is found. Further, the neutrality hypothesis is confirmed among the remaining variables. Paying particular heed to SSA, as the third paper is titled "Causality analysis among FDI, renewable electricity output (REO), and GDP: Evidence from SSA". The paper uses the panel vector autoregression generalized method of moment model and found that REO predicts/causes GDP growth and vice versa. Thus, the feedback hypothesis is confirmed. Also, no causal effect was revealed between FDIREI-REO and FDIREI-GDP. To intensify research on Africa's green power, the fourth paper, "Determinants of Renewable Electricity Generation (REG) in Africa: A Focus on FDI", is introduced. To date, the impact of FDI on REG in Africa has yet to be investigated. By using the Prais- Winsten panel corrected standard errors model, the study finds compelling evidence that FDI inflows directly and indirectly limit, or even impede, the REG's development. The African population growth undermines REG. However, the encouraging result is that raising African awareness of renewable energy boosts REG. The fifth paper, "FDI and the Gap of Clean Power Finance: The Case of Africa", theoretically addresses the determinants of the clean energy financing gap and the Paris Agreement's impact on green FDI. The research found that the Paris Agreement attracts clean FDI. However, the gap is mainly attributed to corruption, underdeveloped policies, and the absence of accurate data. Moving forward, focused and diverse policy implications are outlined in the thesis.